Effect of Irrigation on the Yield and Quantity of Potato Varieties - Ábrahám, Babett Éva; Sárvári, Mihály (Acta Agraria Debreceniensis, 2005)
In Hungary, the growing area of potato area dropped dramatically in the last few decades. Additionally not only are we lagging behind Western European countries as regards yields, but the competitiveness of production is further decreased by the great alternation in yields from year to year, unpredictable market conditions, poor consumption habits and, often the lack of quality products.The experiment was carried out at the experimental site of the University of Debrecen, Farm and Regional Research Institute, at Látókép. In our experiment, we examined the yield and some quality parameters of 9 medium-early varieties in large parcels. Of the examined varieties, 3 are of Dutch, and 6 are of Hungarian breeding.The experiment was set up in 2003 and 2004, in two years of significantly different precipitation, on 50 m2 parcels on calcareous chernozem soil after winter wheat as a forecrop in both years. The 9 varieties were examined in 4 repetitions in randomized blocks, from which two repetitions were irrigated, and two were non-irrigated.We examined the yields of the varieties, the distribution of tubers according to size and their percentages, and the changes in specific parameters of quality and inner content due to irrigation. We studied the dry matter content, the starch content, the underwater mass, the amount of reducing sugars, and the colour index of frying of the tubers.In Summary, it can be stated that among the agrotechniques, year effect, variety and irrigation factors have considerable impact on potato yield quality and quantity. However the effect of irrigation depends on the crop year. In a draughty year, like in 2003, irrigation could increase the yield by 10%, while in a more favourable wet year, the improving effect of irrigation was low.